A new multi-objective model of agile supply chain network design considering transportation limits. Issue 1 (1st January 2019) - Mahmoodi, Mahdi
ABSTRACT: In this research, a triple-objective model with the assumption of multi-material and multi-product in five stage of supply chain network (SCN) is introduced. A five-stage supply chain network includes the following: supplier, manufacturer, retailer and distributor as well as customer zone. The goal is to determine production and supply quantity in each node of supply chain network under stochastic demand of a competitive market. The first objective is minimizing the expenses such as transportation, inventory, shortage and production. The second objective is minimizing the risks in each node as well as route of supply chain network which means considering customer risk in each customer zone and making a connection with supplier zone regarding the SCN routs. The third objective is maximizing flexibility which leads to a restraint model in fluctuation of the market demand. Having the constraints in mind, transportation volume, transportation speed and transportation vehicle are taken into account. The capacity of production is considered with respect to the demands of nodes in the next stage. The inventory and shortage are considered as the constraints of the step. In the final step, a network with different number of nodes is designed which brings about the use of modified NSGA-II regarding the multi-encoding. The results display flexibility effect in supply chain network which dominates the uncertainty situation of the market and a better restraining approach for SCN.